2006
DOI: 10.1093/ps/85.7.1212
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid availability and true metabolizable energy content of corn distillers dried grains with solubles in adult cecectomized roosters

Abstract: Five sources of corn distillers dried grains with solubles (DDGS), which varied in darkness of color, were collected from several processing plants in the Midwestern United States. Sources of DDGS were analyzed for their amino acid and energy contents, measured for color score, and evaluated for TMEn, apparent amino acid digestibility, and true amino acid digestibility. A precision-fed rooster assay was used, in which each DDGS sample was tube fed (25 g) to adult cecectomized roosters, and the excreta were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 7 publications
7
63
2
8
Order By: Relevance
“…The highest deviations were observed for DDGS, which might also reflect recent improvements of the method of production of these byproducts still not considered in Feed Tables. In the same way, recent work in poultry (Batal and Dale, 2006;Fastinger et al, 2006) has reported AMEn values for corn DDGS even higher than those obtained in the current study.…”
Section: Average and Standard Deviation Of Amen Values In The Feedstusupporting
confidence: 80%
“…The highest deviations were observed for DDGS, which might also reflect recent improvements of the method of production of these byproducts still not considered in Feed Tables. In the same way, recent work in poultry (Batal and Dale, 2006;Fastinger et al, 2006) has reported AMEn values for corn DDGS even higher than those obtained in the current study.…”
Section: Average and Standard Deviation Of Amen Values In The Feedstusupporting
confidence: 80%
“…Salim et al (2010) reported that the average CP content in DDGS from different samples was 27.15% with 3.72% coefficient of variation. Furthermore, Batal and Dale (2006) and Fastinger et al (2006) reported similar results (CP ranged from 23-32%). Using 10 new ethanol plants in Minnesota and South Dakota, Spiehs et al (2002) have evaluated nutrient level of DDGS originating from these plants.…”
Section: Nutritional Value and Bioavailability Of Ddgssupporting
confidence: 56%
“…Ethanol production from maize generates large amounts of nonextractable seed material, called dried distiller grain solubles (DDGS; Rausch and Belyea, 2006), the production of which progressively increased in recent years. Historically, most of the DDGS has been fed to cattle, but in the past several years, researchers have been evaluating its nutritional value and feeding recommendations for swine and poultry (Fastinger et al, 2006;Pedersen et al, 2007). Hence, research projects under way could modify the amino acid composition, protein composition, and phosphorous content of DDGS (Singh et al, 2005;Rausch and Belyea, 2006).…”
Section: Future Goals and Opportunitiesmentioning
confidence: 99%